Urban Informatics - Shi, Wenzhong; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
Urban Informatics (UI) is an open-access, peer-reviewed journal publishing high-quality, original research on urban informatics, including urban system, theories, methods, and technologies for urban big data acquisition, infrastructure and analytics, as well as new solutions to urban problems and applications. The scope of Urban Informatics includes but is not limited to Cutting-edge research that leverages emerging technologies (e.g., ICTs, AI, IoT, UAV) and data in the context of urban environments Advance science of cities through data and technologies Research that tackles the relationships among people, place and technologies in cities Research that focuses on the social and human implications of technology in cities Research that tackles sustainable smart cities development Technologies, theories, and models for urban research Provide solutions to various urban problems and applications.
Keywords: Geographic information systems; Human geography; Social sciences$1 (BData processing.s; Geographical Information System; Human Geography; Computer Application in Social and Behavioral Sciences